Mechanical Response of FeNiCrCoAl High-Entropy Alloys at the Nanoscale: Predictions from Molecular Dynamics - Ernesto Amaro; Joaly Delgado-Alvarez; Jairo Andrés Martínez-Uribe; Sergio Mejía-Rosales (Nanomaterials)
The mechanical response of high-entropy alloys (HEAs), specifically the FeNiCrCoAl HEA, was studied at both bulk and nanoparticle scales using molecular dynamics simulations. These simulations were performed using the LAMMPS software with an Embedded Atom Method (EAM) potential. The results show that Bulk HEAs exhibited enhanced hardening and plasticity, while in nanoparticles, distinct deformation patterns were observed, including nanotwin formation, V-shaped stacking fault planes, and intermittent dislocation activity due to free surface effects. The crystallographic orientation with respect to the compression significantly affected the deformation mechanisms, with the [100] direction favoring progressive hardening, while the [110] and [111] directions exhibited different stacking fault and dislocation dynamics. A detailed analysis using von Mises stress and dislocation analysis provided insights into the effects of scale on mechanical properties.